(untitled) (World Bulletin of Public Health, 2022)
The recent novel coronavirus disease 2019 which is caused by SARS-COV2, is the midst of worldwide panic and global health concern since December, 2019. It has been spread dramatically all over the world and became an important global crisis. It is reported that SARS-COV2 infection, in persons with underlying comorbidities have an increasingly bad progression that often-causing death. This retrospective comparative study aims to evaluates some of comorbid conditions in correlation to severity of COVID-19. 400 COVID-19 patients have been recruited from Al-Diwaniyah teaching hospital- Iraq, from 1st of December, 2020 until the end of January, 2021. From what is known of the epidemiological data, COVID-19 patients’ who have a comorbidity, such as diabetes mellitus and hypertension, are more likely to develop more severe progression of the SARS-CoV2 infection also, older patients, especially those 65 years and above who have comorbidities and are infected, are more susceptible to get wars manifestations. Patients with chronic disease should take all necessary precautions to avoid SARS CoV-2 infection and should take a good medical care.